South Africa's financial services trade and trade potential under the African Continental Free Trade Area - Gyan, Mawuko (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
This study investigates the nature, importance and prospects for growth of South Africa's trade in financial services and trade potential under the African Continental Free Trade Area (AfCFTA) Agreement. It does so by identifying and measuring the share, growth performance and some of the characteristics of South Africa's financial services trade in the aggregate and with selected trading partners and regions. It also computes South Africa's trade potential in financial and finance-related services trade with selected African trading partners amid the ongoing AfCFTA services trade negotiations, using trade complementarity indices (TCIs). Finally, the study estimates the effect of regional trade agreement participation on bilateral financial services trade involving African economies using a gravity model. The study employs the use of descriptive trade statistics to analyse the share and growth performance of South Africa's services trade in the aggregate and at the sub-sector level, based on balance of payments (BOP) data for the years 2005 to 2022 from the ITC, UNCTAD and WTO Trade in Services Database. Bilateral trade data from the OECD and WTO BaTIS Database is also used in the analysis of intra-African trade. In order to investigate trade through Mode 3, information on FDI statistics is sourced from recent reports. Through analysing trade complementarity indices (TCIs), the study finds that South Africa has significant potential to increase exports of financial and finance-related services to Mauritius, Ghana and the SADC and non-TFTA regions. South Africa has significant import TCIs with the COMESA and non- TFTA regions as well as Egypt, Tunisia and Kenya. The gravity model estimation reveals that membership in African regional groupings like the AfCFTA, SADC, COMESA and the EAC have no significant positive impact as yet on intra-African financial services trade.
Keywords: Trade finance; South Africa Commerce; African Continental Free Trade Area; Gravity model of international trade